2020
DOI: 10.1084/jem.20191131
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine promotes brain metastasis by polarizing microglia and suppressing innate immune function

Abstract: Up to 40% of lung cancer patients develop brain metastasis, and the median survival of these patients remains less than 6 months. Smoking is associated with lung cancer. However, how smoking impacts the development of brain metastasis remains elusive. We examined 281 lung cancer patients with distant metastasis and found that smokers exhibited a significantly high incidence of brain metastasis. We found that nicotine enhanced brain metastasis, while a depletion of microglia suppressed this effect in vivo. Nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 81 publications
2
67
1
Order By: Relevance
“…Additionally, previous studies suggested that DNA damaging factors like smoking history and nicotine consumption could suppress innate immune function and promote lung cancer brain metastasis. 51 , 52 However, our results showed no difference in the proportion of distant metastasis between high and low EXO1 expression groups in our cohort, possibly due to the small size of cases. Interestingly, as an outstanding enriched pathway in KEGG, neuroactive ligand-receptor interaction was reported to be closely related to smoking-induced lung cancers.…”
Section: Discussioncontrasting
confidence: 64%
“…Additionally, previous studies suggested that DNA damaging factors like smoking history and nicotine consumption could suppress innate immune function and promote lung cancer brain metastasis. 51 , 52 However, our results showed no difference in the proportion of distant metastasis between high and low EXO1 expression groups in our cohort, possibly due to the small size of cases. Interestingly, as an outstanding enriched pathway in KEGG, neuroactive ligand-receptor interaction was reported to be closely related to smoking-induced lung cancers.…”
Section: Discussioncontrasting
confidence: 64%
“…TAMs polarize towards M2 type through the IL-6/STAT3 signaling pathway to promote tumor metastasis and rejects immune cells from penetrating ( 108 110 ). Wu SY et al proved that M2 macrophages are closely related to brain metastasis of lung cancer ( 111 ). On the other hand, by regulating mTOR, TAMs block normal glycolysis, induce excessive angiogenesis, and form abnormal blood vessels ( 112 ).…”
Section: Mechanism Of Lung Cancer Driver Genes In Brain Metastasismentioning
confidence: 99%
“…Despite the lack of carcinogenicity evidence, it has been reported that nicotine promotes tumour cell survival by decreasing apoptosis and increasing proliferation [ 49 ], indicating that it may work as a “tumour enhancer”. In a very recent study, chronic administration of nicotine to mice (1 mg/kg every 3 days for a 60-day period) enhanced brain metastasis by skewing the polarity of M2 microglia, which increases metastatic tumour growth [ 50 ]. Assuming that a conventional cigarette contains 0.172–1.702 mg of nicotine [ 51 ], the daily nicotine dose administered to these animals corresponds to 40–400 cigarettes for a 70 kg-adult, which is a dose of an extremely heavy smoker.…”
Section: Introductionmentioning
confidence: 99%